Photoluminescence characteristics of CdSe quantum dots: role of exciton–phonon coupling and defect/trap states. (12th July 2017) - Kushavah, Dushyant; Mohapatra, P K; Ghosh, Pintu; Singh, Mamraj; Vasa, P; Bahadur, D; Singh, B P
Abstract: In this paper, we report temperature dependent photoluminescence (PL) characteristics of CdSe colloidal QDs with average diameter ~2.8 nm. Temperature dependence of strongly confined exciton PL peak position, linewidth and intensity were investigated in 30 K to 300 K temperature range. Our studies reveal nearly four times weaker exciton-LO phonon coupling than bulk CdSe crystal. Theoretically, it should be vanishingly small due to near identical electron and hole charge distributions in strongly confined QDs. On the other hand, exciton-acoustic phonon coupling is an order of magnitude larger than its bulk counterpart. Observed finite value of exciton-LO phonon coupling and enhanced exciton-acoustic phonon coupling are due to piezoelectric strain fields. PL intensity exhibits anomalous behavior in the temperature range 100–230 K. This has been explained by thermally activated detrapping of the charge carriers trapped in the potential wells formed at the interface adjoining dislocations/stacking faults developed during the synthesis process. Above 230 K, PL is partially quenched by thermal escape of charge carriers from luminescing exciton state to higher lying nonluminescing states.